Analytical CRM model aimed at retail inventory optimization - Dukić, Branimir; Martinović, Martina; Dukić, Stojana (Oeconomica Jadertina, 2017)
Customer relationship management is a modern business philosophy that grew out of relationship marketing focusing on a consumer as an individual, i.e. on satisfying consumer needs in order to foster their loyalty and turn them into repeat customers. Although the primary goal of customer relationship management is to ensure the stability of revenue generation from a long-term partnership between a supplier and a consumer, it is also a philosophy that rationalizes operations primarily through reducing the costs of attracting new customers, thereby optimizing inventories. Inventory optimization involves adjusting the production process to the needs of consumers. In the modern retail environment, characterised by high level of competition, maintaining inventories not readily marketable can mean the difference between survival and going out of business. Therefore, modern retail systems tend to optimize inventory. Today, this would be impossible to do without the possibilities provided by CRM systems, in particular its subsystem, analytical CRM. Monitoring consumer behaviour in retail is within the scope of CRM system. Data obtained from such systems serve as the basis for inventory management. However, for inventory management to be possible, one has to consider which models, especially stochastic, can be used in inventory optimization. These models then need to be applied in the analytical subsystem of the CRM system. For such models to have use value, it is necessary to adjust the transaction part of the CRM system in terms of collecting the data needed for selected retail inventory optimization models. The answers to these and other questions relating to the use of analytical CRM in optimizing retail inventory are contained in the results of this research.
Keywords: Relationship marketing; customer relationship management; consumer; customer; retail; inventory optimization